EDUKASI RISIKO STUNTING MELALUI PEMERIKSAAN KADAR HB CALON PENGANTIN DI KUA KABUPATEN BENGKULU TENGAH - Welkriana, Putri Widelia; Farizal, Jon; Laksono, Heru (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2024)
Women of childbearing age are susceptible to anemia due to several factors such as the menstrual cycle, lack of nutritional and iron intake, and pregnancy. Anemia in pregnant women increases the risk of premature birth, maternal and child death, infection, and stunting in toddlers. It is important to carry out initial screening of hemoglobin levels in women of childbearing age before marriage who will be facing pregnancy as an initial diagnosis of pregnancy anemia to prevent anemia in pregnant women. Results of the 2010 Riskesdas, the prevalence of stunting in Indonesia is still high, namely 36.5%. The five provinces with the highest prevalence of stunting in Indonesia are East Nusa Tenggara (58.4%), West Papua (49.2%), West Nusa Tenggara (48.2%), North Sumatra (42.3%), and West Sulawesi (41.6%). In Aceh Province, a fairly high prevalence was also found, namely 39%. Meanwhile, in the 2013 Riskesdas results, the national prevalence of stunting among school-age children was 30.7% (12.3% were very stunted and 18.4% were stunted). This community service is carried out to provide insight and knowledge to the community, especially teenagers, in recognizing the risk factors for stunting and the benefits of supporting examinations in detecting stunting conditions from an early age, so that it is hoped that every community can carry out prevention, especially for teenagers who have a lot of activities